Perancangan Program Penjualan Berbasis Web Pada CV. Buana Jaya Utama Jakarta - Yani, Ahmad; Munir, M.Sirozul (Akasia: Artikel Ilmiah Sistem Informasi Akuntansi, 2023)
Abstract-Currently, business development can no longer only rely on conventional systems, but must also use systems that already utilise information technology that can provide online sales services. So that business development will be faster, more efficient and effective. Therefore, in this study the authors discuss the design of a web-based sales programme at CV.Buana Jaya Utama Jakarta. The aim is to expand the company's marketing reach, collect and analyse customer data, and facilitate the management of stock items. Some of the problems faced by the company include limited marketing reach, sales process efficiency, stock management, limited data analysis, and system integration. The research methods used include observation, interviews, and literature studies, using a spiral system development model. The scope of this research is limited to stock management, buying and selling transactions, and point of sale system. The web-based sales programme to be designed will use the PHP programming language with the Laravel framework. The programme's access rights will be divided into user and admin to facilitate purchasing, reviewing item data, managing stock items, and confirming purchases. Keywords: Web-based sales program design, CV Buana Jaya Utama Jakarta, Stock management